Peran Kode Etik Guru sebagai Landasan Berprilaku dalam Pengembangan Pendidikan - Roza Fitri Yenti; Astuti Darmiyanti (Journal on Education, 2023)
The teacher is a figure whose role is needed in the world of education. Teachers are expected not only to transfer knowledge, but are able to educate and direct the development of the character and personality of students. A teacher must have a personality that reflects a teacher who deserves to be emulated, where the teacher's code of ethics is used as a reference/guideline. The purpose of this study was to determine the role of the teacher's code of ethics as a basis for behavior. This research method uses descriptive qualitative analysis with a library research approach, namely by collecting material from both books and journals that support this research. The teacher's code of ethics is the moral foundation and code of conduct for teachers in carrying out their work related to educating, teaching, guiding, training and directing students. In some literature it is explained that the teacher's code of ethics is intended as a guide to behavior or as a controller for teachers in carrying out their profession. Based on this, it can be concluded that the teacher's code of ethics influences the development of education.